Identifikasi Tingkat Pengetahuan Masyarakat Tentang Beyond Use Date (Bud) Pada Sediaan Obat Di Rt 002/002 Kelurahan Pinang Kota Tangerang - Imansari, Aulia Nadya Rizki; Sayyidah, Sayyidah; Khoirani, Anisah Putri (Sekolah Tinggi Ilmu Kesehatan Widya Dharma Husada Tangerang, 2025)
Public knowledge regarding the expiration of medications after opening or compounding, known as Beyond Use Date (BUD), remains relatively low. BUD plays a crucial role in maintaining the quality, effectiveness, and safety of medications. This study aims to describe the level of public knowledge about BUD in pharmaceutical preparations in RT 002/002, Pinang Subdistrict, Tangerang City. This research employed a descriptive quantitative method with purposive sampling and involved 100 respondents. Data were collected using a questionnaire and analyzed using frequency distribution and percentages. The results showed that most respondents had a moderate level of knowledge (50%), followed by good (24%) and poor (26%) levels. The majority of respondents were aged 17–25 years, female, held a higher education degree, and obtained information about BUD mainly from the internet. It can be concluded that public knowledge regarding BUD still needs improvement, particularly through proper education and information dissemination.